Ridge Split Techniques: A Literature Review - Mohit Das; Abhaya Chandra Das; Sourav Panda; Rashmita Nayak; Rinkee Mohanty; Anurag Satpathy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Extraction of teeth leads to loss of alveolar bone in several patterns. The bone loss can occur in a horizontalor vertical direction or a combination of both. Horizontal ridge width deficiency possesses a challenge for theclinician to obtain primary stability during loading and there is risk of fracture of bone segment. Thereforedifferent techniques have been described to gain the ridge width. One of the techniques used is ridge splittechnique which was first described by Simion et al in 1992. It is a technique of bone manipulation in sucha way that it becomes a site for implant placement without removing any bone. Various types of techniqueslike 3 staged approach, one staged approach etc are described for various sites and situation that help inobtaining an adequate width for loading. This article specifically deals with the different types of ridge splittechniques and its description in a simplified manner.